Hexagonal Boron Nitride as Anode for Sodium-Ion Battery – A Reality Check!. Issue 2 (28th February 2023) - Garg, Shubham; Parmar, Avanish Singh; Rosy,
Abstract : Sodium-ion batteries (SIBs) have gained enormous attention as an alternative electrochemical energy storage system. A significant challenge for its practical viability is finding an anode material that can provide high specific capacity along with good cycling stability. Recently, numerous theoretical works have proposed hexagonal boron nitride (hBN) as a promising anode material for SIBs. Nevertheless, there has been no reported experimental verification for the said theoretical claims. To fill the knowledge gap, here, the electrochemical performance of hBN has been investigated under the capacity of a potential anode for SIBs. The effect of particle morphology on the electrochemical performance of hBN has also been investigated using bulk hBN powder and nanoplatelets hBN as active materials. Unexpectedly, hBN showcased minimal charging capacity with effectively no reversible intercalation/de-intercalation of Na-ions. The obtained results provide experimental insight into the ineffectiveness of hBN in serving as SIB anode material, unlike the previous theoretical claims. We believe it is essential to report these discrepancies in the computational and experimental findings for the benefit of experimentalists working enthusiastically to explore and develop new anode materials related to boron nitride systems.